Psikoedukasi untuk meningkatkan pengetahuan orang tua dalam mengembangkan kemandirian rawat diri anak berkebutuhan khusus - Nurul Fitri Alimah (Universitas Muhammadiyah Malang, 2022)
The community in this case is parents with children with special needs totaling 30 people who have children with special needs with age ranges of 3-12 years. The problem that occurs is that parents do not understand how to teach children in terms of self-care, so that children are less independent in self-care such as toileting, dressing and eating independently. The purpose of this intervention is to provide psycho-education to parents to improve parents' knowledge and skills on how to teach self-care to children with special needs through 15 cadres. The assessment uses for interviews, questionnaires, and checklist. The intervention used is psycho-education with the lecture method. The results of the intervention was of cadres increased in terms of their knowledge about the independence of self-care for children with special needs. The average value of the pre test is 4.8667 and the post test is 10.6000. After the intervention, parents also better understand what is meant by self-care for children with special needs and apply it to their children.